2019
DOI: 10.1101/703512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiota structure differs between honey bees in winter and summer

Abstract: 24Adult honey bees harbor a specialized gut microbiota of relatively low complexity. While 25 seasonal differences in community composition have been reported, previous studies have 26 focused on compositional changes rather than differences in absolute bacterial loads. 27 Moreover, little is known about the gut microbiota of winter bees, which live much longer 28 than bees during the foraging season, and which are critical for colony survival. We 29 quantified seven core members of the bee gut microbiota i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
(5 reference statements)
2
11
0
Order By: Relevance
“…Frischella perrara was more abundantly detected in spring, which is in accordance with the findings of previous studies (Kešnerová et al, 2020). Functional annotation of the autumn-specific bacteria identified functions related to carbohydrate metabolism, amino acid process and transport, and transposition.…”
Section: F I G U R Esupporting
confidence: 91%
See 1 more Smart Citation
“…Frischella perrara was more abundantly detected in spring, which is in accordance with the findings of previous studies (Kešnerová et al, 2020). Functional annotation of the autumn-specific bacteria identified functions related to carbohydrate metabolism, amino acid process and transport, and transposition.…”
Section: F I G U R Esupporting
confidence: 91%
“…), and the presence of additional noncore members ( Frischella perrara , Bartonella apis ) (Engel et al, 2012; Jones et al, 2018). Interestingly, recent studies also revealed individual‐specific microbiomes, reflecting potential roles in adaptive functions, such as fluctuation of metabolic potential and nutritive resources across seasons, as well as social status (Ellegaard & Engel, 2019; Kešnerová et al, 2020; Yun et al, 2018). Honeybee pathogens, such as Varroa destructor , brood diseases and Nosema ceranae , are detected mainly by hive inspection and conventional PCR, which often leads to delayed treatment initiation (López‐Uribe et al, 2020; Samuelson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Alpha2.1 persisted in the gut environment and even significantly increased relative 627 to foragers and nurses sampled in summer (Kešnerová, et al 2019). The same pattern 628 was also observed for another community member of the bee gut microbiota, 629…”
Section: Discussionmentioning
confidence: 64%
“…Adult honeybees harbour specialized gut microbiota of relatively low complexity with five core bacterial strains [3,4,24,25,26]: Lactobacillus Firm-4 and Firm-5 (Firmicutes), Giliamella (γ-proteobacteria, Orbales), Snodgrassella (γ-proteobacteria, Neisseriaceae), Bifidobacterium (Actinobacteria) and a number of elective bacterial strains, including Frischella (γ-proteobacteria, Orbales), Bartonella (α-proteobacteria, Rhizobiales), Commensalibacter (α-proteobacteria, Acetobacterales) and Bombella (α-proteobacteria, Acetobacterales), which was also confirmed in this study (Figure 1, Figure 2 1, Table 1, Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The next-generation sequencing (NGS) is a culture-independent method often used for studding entire microbial communities and helps to understand how microbes influence health and diseases of humans and animals including a honeybee [1][2][3]. Adult honeybees harbor a specialized gut microbiota of relatively low complexity with diet as a major factor to differences in bacterial loads [4]. Although honeybee microbiome core species is quite consistent regardless of environmental, geographical and genetic differences between specimens [2], some studies indicated that it can be sensitive to infections, changes in diet, malnutrition and many anthropogenic activities, as extensive pesticide use and urban land-use changes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%